Anagrelide reduces thrombotic risk in essential thrombocythaemia vs. hydroxyurea plus aspirin. (19th September 2016) - Dombi, Péter; Illés, Árpád; Demeter, Judit; Homor, Lajos; Simon, Zsofia; Karadi, Eva; Udvardy, Miklos; Egyed, Miklos
Abstract: Objective: To evaluate the reduction in thrombotic events (TE) in patients with essential thrombocythaemia (ET) treated with anagrelide versus hydroxyurea + aspirin (HU + ASA). Methods: A questionnaire was developed using 2008 WHO diagnostic criteria, and thrombotic risk factors were stratified according to Landolfi criteria. Through questionnaire completion, clinicians at Hungarian haematological centres entered data into the Hungarian MPN Registry on patients with myeloproliferative neoplasms. Based on ET registry data, TEs in anagrelide‐treated patients ( n = 139) were compared with HU + ASA‐treated patients ( n = 141). Results: Patients were followed up for (median) 6 yr. TEs were reported in significantly fewer anagrelide‐treated patients versus HU + ASA (15.1% versus 49.6%; P < 0.001). Numbers of major arterial and major venous events were similar between the groups, although there were over fivefold more minor arterial and minor venous events in the HU + ASA group ( P < 0.001). While median age at diagnosis was older and length of follow‐up shorter in the HU + ASA group ( P < 0.05), this did not influence TE incidence; medication and TE before diagnosis only influenced TE incidence. Conclusions: Anagrelide significantly decreased the number of patients experiencing minor arterial and minor venous TEs versus HU + ASA over 6 yr. Risk of TE after diagnosis was significantly increased if the patient had TE before diagnosis.